Left ventricular remodelling, and systolic and diastolic function in young adults with β thalassaemia major: a Doppler echocardiographic assessment and correlation with haematological data - Bosi, G; Crepaz, R; Gamberini, M R; Fortini, M; Scarcia, S; Bonsante, E; Pitscheider, W; Vaccari, M (Heart (British Cardiac Society), 2003)
Objective: To evaluate left ventricular morphology and function in a large population of patients with β thalassaemia. Design: Echo Doppler assessment of left ventricular function and correlation of cardiovascular data with haematological data. Setting: Thalassaemia unit in a tertiary referral centre. Patients: 197 young adults with β thalassaemia, following an adequate transfusional and chelation treatment regimen, without clinical signs of cardiopulmonary involvement. The control group consisted of 213 healthy subjects. Results: Left ventricular volumes, mass index, and mass/volume ratio were increased. Diastolic and systolic shapes were different, the left ventricle maintaining an ellipsoidal shape. The ejection fraction was reduced, and was < 50% in 33 patients. Stroke volume and cardiac index were increased, and systemic vascular resistance was decreased. Fractional shortening and mean velocity of circumferential shortening were decreased. Meridional end systolic and peak systolic stress were increased, as was circumferential end systolic stress. The contractile state was reduced while the functional preload index did not differ. Left ventricular diastolic function, evaluated from the mitral inflow, showed a slightly prolonged isovolumic relaxation time, increased flow velocity integrals, and an increased E/A ratio. Among the haematological data, only serum ferritin showed a weak negative correlation with left ventricular ejection fraction. The patients with the highest serum ferritin (> 2500 ng/ml) had the lowest ejection fraction. Conclusions: Patients with β thalassaemia on an adequate transfusion and chelation treatment regimen show abnormal left ventricular remodelling with increased volumes, mass, and mass/volume ratio. Systolic chamber function and contractile state are reduced, with a slightly increased afterload. These findings seem mainly to be related to the increased cardiac output caused by chronic anaemia. Left ventricular performance is better preserved when chelation treatment is adjusted to maintain the serum ferritin concentration at < 1000 ng/ml.